2015 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2015
DOI: 10.1109/icassp.2015.7178830
|View full text |Cite
|
Sign up to set email alerts
|

Learning feature mapping using deep neural network bottleneck features for distant large vocabulary speech recognition

Abstract: Automatic speech recognition from distant microphones is a difficult task because recordings are affected by reverberation and background noise. First, the application of the deep neural network (DNN)/hidden Markov model (HMM) hybrid acoustic models for distant speech recognition task using AMI meeting corpus is investigated. This paper then proposes a feature transformation for removing reverberation and background noise artefacts from bottleneck features using DNN trained to learn the mapping between distant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The results for systems without applying fMLLR have been previously reported in [22]. Compared to the baseline performance, BN-based system improves the performance on SDM while trained on IHM data by 12.6% absolute WER (from 76.0% to 63.4%; 16.5% relative), whilst a minor degradation of 1.5% absolute (4.5% relative) is observed on the matched condition.…”
Section: Single-condition Mapping Using Sdmmentioning
confidence: 70%
See 4 more Smart Citations
“…The results for systems without applying fMLLR have been previously reported in [22]. Compared to the baseline performance, BN-based system improves the performance on SDM while trained on IHM data by 12.6% absolute WER (from 76.0% to 63.4%; 16.5% relative), whilst a minor degradation of 1.5% absolute (4.5% relative) is observed on the matched condition.…”
Section: Single-condition Mapping Using Sdmmentioning
confidence: 70%
“…Our previous work showed that SDM system trained using alignment generated from IHM (clean) ASR system provided significantly better performance [22], compared to SDM system trained using alignment from SDM. Since SDM data are synchronized with IHM data (on a frame-level), the SDM models are trained using HMM state alignments generated for IHM recordings.…”
Section: Experimental Data and Setupmentioning
confidence: 99%
See 3 more Smart Citations